2015
DOI: 10.1111/1758-2229.12261
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and microbial content of the driest site of the hyperarid Atacama Desert, Chile

Abstract: The Atacama Desert is the driest and oldest desert on Earth. Eleven years ago, the Yungay region was established as the driest site of this hyperarid desert and also close to the dry limit for life on Earth. Since then, much has been published about the extraordinary characteristics of this site and its pertinence as a Mars analogue model. However, as a result of a more systematic search in the Atacama here, we describe a new site, María Elena South (MES), which is much drier than Yungay. The mean atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 19 publications
4
63
1
Order By: Relevance
“…The hyperarid soils are characterized by community profiles dominated by Actinobacteria (67% to 86% relative abundance [RA]), Chloroflexi (4.2% to 9.7% RA), Proteobacteria (2.2% to 15.9% RA), and Gemmatimonadetes (0.5% to 7.9% RA). This distribution is similar to that observed previously in hyperarid regions of the Atacama (24, 25, 41, 42) as well as in global deserts, including the McMurdo Dry Valleys of Antarctica and the Tataouine Desert (18). An intriguing pattern emerged from the analysis of Atacama hyperarid sites.…”
Section: Resultssupporting
confidence: 89%
“…The hyperarid soils are characterized by community profiles dominated by Actinobacteria (67% to 86% relative abundance [RA]), Chloroflexi (4.2% to 9.7% RA), Proteobacteria (2.2% to 15.9% RA), and Gemmatimonadetes (0.5% to 7.9% RA). This distribution is similar to that observed previously in hyperarid regions of the Atacama (24, 25, 41, 42) as well as in global deserts, including the McMurdo Dry Valleys of Antarctica and the Tataouine Desert (18). An intriguing pattern emerged from the analysis of Atacama hyperarid sites.…”
Section: Resultssupporting
confidence: 89%
“…In 2015 we reported the discovery of Maria Elena South (22°15′39′′S, 69°43′29′′W) the driest site of the already hyperarid Atacama (Azua-Bustos et al, 2015). We found that soil samples from Maria Elena South showed extremely low, albeit variable levels of organics (0.1–1.1%.…”
Section: What Has Been Reported About Organic Carbon and Life In The mentioning
confidence: 99%
“…It is bordered on the east by the Andes Mountains and on the west by the Coastal Range. The Atacama is well known for being the driest (McKay et al, 2003; Azua-Bustos et al, 2015) and oldest desert on Earth, estimated to be arid of the past 150 million years and hyperarid for the past 15 million years (Pueyo et al, 2001; Houston and Hartley, 2003; Hartley et al, 2005; Rech et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…per gram soil with the lowest values observed in the rhizosphere soils of Atacama Desert. This is a hyperarid ecosystem where low numbers of bacteria (from 1 × 10 2 to 3 × 10 5 CFU g −1 soil) and low amount of extractable DNA (<1.2 μg DNA g −1 of soil) from soil have been reported (Azua-Bustos et al 2015;Jorquera et al 2014;Maier et al 2004). However, Fletcher et al (2011) observed similar Fig.…”
Section: Discussionmentioning
confidence: 99%